Reconfiguring Professional Inequality: Organizational Identity and Stratification in the Nigerian Accounting Profession - Taiwo A. Muritala (International Journal of Social Science and Religion (IJSSR), 2026)
This study critically examines how organizational identity, meritocratic evaluation, and commercialization intersect to reproduce professional inequality within the Nigerian accounting profession. Employing a qualitative research design, it draws on document analysis and in-depth interviews with accounting professionals across diverse firms. Thematic analysis identifies four interrelated mechanisms. First, a dominant discourse of neutrality and technical objectivity obscures underlying power relations within the profession. Second, merit-based evaluation systems privilege elite educational credentials and embedded social capital, thereby reinforcing stratified access to career advancement. Third, intensifying commercialization pressures prioritize revenue generation and client acquisition, reshaping professional norms and performance expectations. Fourth, discursive strategies are mobilized to legitimize and normalize exclusionary outcomes. The findings demonstrate that organizational identity functions not merely as a symbolic construct but as a material and institutional mechanism structuring access to opportunities, recognition, and rewards. While meritocracy and market-oriented logics are framed as neutral and efficiency-driven, they operate in practice as instruments that reproduce structural inequalities. This study contributes to critical debates on professional stratification and institutional power, and calls for targeted interventions by policymakers and professional bodies to balance market imperatives with inclusion, thereby fostering more equitable career progression.